Evaluating Exercise as Evidence-Based Practice for Individuals with Autism Spectrum Disorder - Dillon, Suzanna R.; Adams, David; Goudy, Leah; Bittner, Melissa; McNamara, Scott (Frontiers in Public Health, 2017)
Background: The purpose of this study was to conduct a systematic review of the literature to evaluate empirical support for the use of exercise as an evidence-based practice (EBP) for individuals with autism spectrum disorder (ASD), aged 1 to 21 years, using the Adapted Physical Activity Taxonomy (APAT)1. Method: A systematic review of research, published within the past 10 years and accessible in SPORTDiscus, ProQuest Nursing, Science Direct, ERIC, Ovid MEDLINE, and PsychINFO databases, was conducted following seven inclusion criteria. An initial 169 articles were identified of which twenty-three articles were found that met the inclusion criteria including implementation of an exercise intervention for participants diagnosed with ASD and utilization of an experimental/quasi experimental, correlational, single subject or qualitative research design. These 23 articles were evaluated using the APAT to determine the quality of the research and the strength of the recommendation in establishing exercise as an EBP. Results: Of the 23 articles evaluated, 17 employed an experimental/quasi experimental design, 1 article employed a correlational design, and 5 articles employed a single subject design. Only 1 article2 was found to meet the minimum overall quality indicator of moderate (i.e., level 2) when evaluated on the APAT. All total, 13 of the 23 articles (57%) had method sections evaluated as weak, and 17 of the 23 articles (74%) had results sections evaluated as weak. Conclusion: From the findings of this systematic review, and in accordance with the Every Student Succeeds Act of 20153 definition of an EBP, it appears that exercise can be considered an EBP for school-aged children with ASD. However, this recommendation is based solely on moderate evidence from one well-designed and well-implemented experimental study, therefore, generalization is still pending further similar findings. Recommendations for future research are offered.